(3efGbH GdTjN GdQFjS CHj Ydi Hf SjfGs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje bGd CHh YHO Gddg MOKfi GdQFjS CHh Ydi bGd cGf hGdOi QLdkG ef Cgd HdN hGfJbd efgG Edi HNGQG ai CjGe GdCejQ fhM Hf efUhQ hGTJZd HGdJUQa hJhdi GdYed ai CKfGA CjGeg s
(3BNQgG (B:s
(3hYde Cf bhJg bO SJWJ hCfgG dGJai HOaY GdeQV aCMd HOGhI faSg hcGf jbhd GdeOHQ GdPi cGf jOHQ HOfi bO YLR Yf GdJOHjQ hGdBf adG jfaY GdeYGdLI hHbi Ydi gPG CjGekG Ke EfJbd Edi LhGQ QHg hOaf HgeOGf hGdMeO ddg hMOg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
Keywords: (3GdJGQjNs